Acquisition of Early Childhood Language Variations in Sociolinguistic Perspectives - Na'imah Na'imah (Indonesian Journal of Early Childhood Education Studies, 2023)
The occurrence of language variation is caused by the variety of speakers and the variety of social interaction activities both in the family, school, and community environment. Sociolinguistics views language as the most important social system and communication system, besides that sociolinguistics, is part of society and culture towards language and its relationship to its use in society. The purpose of this study was to analyze the acquisition of language variations obtained by early childhood in Canden, Jetis, Bantul. The type of research used in this study is descriptive qualitative. The subjects in this study were early childhood. Meanwhile, the object of this study is the acquisition of variations in children's languages. The data collection techniques used are observation, interviews, and documentation. The analysis in this study was using Miles and Huberman. The data obtained are then reduced, presented, and drawn conclusions. Based on the results of the analysis, the results of the study obtained that the form of obtaining language variations in children 3 years old is using Javanese Ngoko, Javanese Kromo, and Indonesian to interact and communicate with others in the daily life of children both in the family environment and in the community environment.